Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Aplikasi Atome di Kalangan Mahasiswa Universitas Surabaya - Andrea Anne Suharsono; Sugeng Hariadi; Mintarti Ariani (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study was to determine the influence of UTAUT 2 (performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, price value and habit) on intention to use of Atome among students at Surabaya University. This study used a quantitative approach and questionnaire data of 100 respondents. The method of analysis in this study uses SEM (Structural Equation Modeling) with SmartPLS version 3. The results of the research conducted show that effort expectancy, facilitating condition, hedonic motivation and habit have a positive and significant impact on intention to use of Atome, then performance expectancy, social influence and price value have no effect on intention to use of Atome.